2014
DOI: 10.1093/mnras/stu2237
|View full text |Cite
|
Sign up to set email alerts
|

Properties of submillimetre galaxies in a semi-analytic model using the ‘Count Matching’ approach: application to the ECDF-S

Abstract: We present a new technique for modelling submillimetre galaxies (SMGs): the 'Count Matching' approach. Using light cones drawn from a semi-analytic model of galaxy formation, we choose physical galaxy properties given by the model as proxies for their submillimetre luminosities, assuming a monotonic relationship. As recent interferometric observations of the Extended Chandra Deep Field-South show that the brightest sources detected by single-dish telescopes are comprised by emission from multiple fainter sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 86 publications
3
50
2
4
Order By: Relevance
“…Our results for stellar and halo masses of bright SMGs and their descendants are a factor of ∼5 lower than those found by Muñoz Arancibia et al (2015). However, their simulations do not selfconsistently predict the sub-mm flux of galaxies as is done in this work, but instead rely on a 'count-matching' approach to link a galaxy's physical properties to its sub-mm flux.…”
Section: Smg Descendants and Environmentcontrasting
confidence: 66%
See 1 more Smart Citation
“…Our results for stellar and halo masses of bright SMGs and their descendants are a factor of ∼5 lower than those found by Muñoz Arancibia et al (2015). However, their simulations do not selfconsistently predict the sub-mm flux of galaxies as is done in this work, but instead rely on a 'count-matching' approach to link a galaxy's physical properties to its sub-mm flux.…”
Section: Smg Descendants and Environmentcontrasting
confidence: 66%
“…Although not shown 8 In Cowley et al (2015), we showed that this confusion effect boosts the cumulative 850 μm number counts by a factor of ∼2 at S 850 μm = 4 mJy for a 15 arcsec FWHM beam. See also Hayward et al (2013) and Muñoz Arancibia et al (2015), who investigate the effect of coarse angular resolution on the observed sub-mm number counts. Fig.…”
Section: Blending Bias In the Angular Clustering Of Single-dish Sourcesmentioning
confidence: 99%
“…SAG model originates from a version of the Munich code (Springel et al 2001) and has been further developed and improved as described in Cora (2006), Lagos et al (2008), Tecce et al (2010a), Orsi et al (2014), Muñoz Arancibia et al (2015) and Gargiulo et al (2015). The latest version of the model is presented by Cora et al (in prep.).…”
Section: Sagmentioning
confidence: 99%
“…However, it is also possible that the sources are merely unrelated galaxies that appear blended due to projection effects (Hayward et al 2013a;Cowley et al 2015;Muñoz Arancibia et al 2015). Spatially resolved spectroscopy is necessary to answer this question definitively, but is not currently available.…”
Section: Spatial Distribution Of Multiple Sourcesmentioning
confidence: 99%